ANALYSIS OF THE EFFECT OF NPL, NIM, NON INTEREST INCOME, AND LDR TOWARD ROA WITH SIZE AS CONTROL VARIABLES (Differences Study on Domestic and Foreign Banks Listed on BEI Period 2010-2015) - Yudha, Aji; Chabachib, Mochammad; Pangestuti, Irene Rini Demi (JURNAL BISNIS STRATEGI, 2017)
This study aims to examine the factors that determine the difference ROA on domestic and foreign banks in Indonesia. The population in this research is data bank domestic and foreign listed on BEI in 2015. The sample used in this research totaled 228 banks. The result of the study showed that, in domestic banks, Non-Performing Loan (NPL) influential negative and significantly to Return On Assets (ROA). Net Interest Margin (NIM) have had a positive impact significantly to Return On Assets (ROA). While Non-Interest Income and Loan to Deposit Ratio (LDR) influential negative but not significantly to Return On Assets (ROA).Category foreign banks Non-Performing Loan (NPL) influential negative and significantly to Return On Assets (ROA). Net Interest Margin (NIM) influential negative and significantly to Return On Assets (ROA). Non-Interest Income influential negative and insignificant to Return On Assets (ROA). Loan to Deposit Ratio (LDR) influential negative and significantly to Return On Assets (ROA). Size proved as a control variable. In this research used chow test to knows the difference between domestic and foreign banks. The result shows that there is no difference between domestic and foreign banks.